Developing supportive policies and strategies for their implementation : student experience with real-world cases - Urbančič, Tanja (2023)
This is a preprint of the following chapter: Urbančič, T.; Orr, D.; Jermol, M.; Amiel, T, Developing supportive policies and strategies for their implementation: Student experience with real-world cases, published in Open Educational Resources in Higher Education: A Global Perspective, edited by J. Olivier and A. Rambow, 2023, Springer, reproduced with permission of Springer Singapore. The final authenticated version is available online at: http://dx.doi.org/10.1007/978-981-19-8590-4.